An International Survey of Steiner/Waldorf Early Childhood Education: Selected Themes and Patterns - Boland, Neil (IASWECE, 2026)
This summary report presents selected findings from an international survey conducted during the centenary year of Steiner/Waldorf early childhood education. Drawing on responses from educators, assistants, leaders and trainers across a wide range of countries and contexts, it offers a descriptive account of participation, respondent demographics and frequently reported needs and challenges. The survey responses point to several areas of concern for participants, including children’s developmental and social needs, family contexts, digital media, collegial and organisational conditions, training, resources and wider questions of sustainability. These findings are presented primarily through graphs and brief summary comments and should be understood as an initial contribution to ongoing reflection and dialogue within the international Steiner/Waldorf early childhood community. This public summary does not provide a full thematic analysis of written responses or regional differences. In particular, responses to the open-text question on how IASWECE can best support early childhood work are not discussed here, as they require more detailed review.
Keywords: Steiner education; early childhood education; Waldorf education; educational research